Recent Publications upon Economics (Quarterly Journal of Economics, 1890)
Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 4, Issue 3, April 1890, Pages 350–356, https://doi.org/10.1093/qje/4.3.350 Published: 01 April 1890